2011
DOI: 10.1186/1756-0500-4-266
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics prescribing practices in oral implantology among jordanian dentists. A cross sectional, observational study

Abstract: BackgroundIn oral implantology, there is no consensus on the most appropriate regimen for antibiotics prescribing, the decision to prescribe antibiotic is usually based on procedure, patient and clinician related factors. The aim of this study was to investigate the rationale of antibiotic prescribing among Jordanian clinicians who practice oral implantology.FindingsThe target sample for the study was the 250 Jordan Dental Implant Group members. A five page questionnaire contained 41 questions, both closed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 26 publications
5
47
1
Order By: Relevance
“…Almost 20 % (n = 41) of those in the penicillin group also recommend a nitroimidazole along with the penicillin agent as an adjunct for anaerobic cover. A similar trend favouring the penicillin group of drugs was found by Abukaraky et al [31] from their survey of dentists in Jordan. Almost 82 % of their study sample also preferred a penicillin drug with amoxicillin and clavulanic acid and amoxicillin being prescribed by 61.5 and 38.5 % respectively.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Almost 20 % (n = 41) of those in the penicillin group also recommend a nitroimidazole along with the penicillin agent as an adjunct for anaerobic cover. A similar trend favouring the penicillin group of drugs was found by Abukaraky et al [31] from their survey of dentists in Jordan. Almost 82 % of their study sample also preferred a penicillin drug with amoxicillin and clavulanic acid and amoxicillin being prescribed by 61.5 and 38.5 % respectively.…”
Section: Discussionsupporting
confidence: 61%
“…The only study with investigation criteria similar to our study was conducted in Jordan and found that only 49.4 % of dentists were in favour of routine antibiotic prescription [31]. The most commonly prescribed pharmacological group of antimicrobial agents by our study sample was the penicillin group (81 %, n = 230) and within this group, almost 50 % (n = 114) prescribed amoxicillin with clavulanic acid as the drug of choice, along with 33.9 % (n = 78) prescribing amoxicillin.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This compares with 50% reported in a similar study with implant practitioners in Jordan. 26 Approximately 85% of respondents reported routinely prescribing an antibiotic pre-operatively and almost 80% postoperatively. The results in this study suggest a wide variation in prescribing patterns with respect to the choice of drug, the dose and the duration for both pre-operative and postoperative prescription (Tables 2-5).…”
Section: Discussionmentioning
confidence: 99%
“…This, however, remains a controversial issue with little high quality evidence to support the routine use of prophylactic antimicrobials in the placing of implants. A recent systematic review 26 concluded that it is still unknown whether postoperative antibiotics are beneficial and which is the most effective antibiotic.…”
Section: Discussionmentioning
confidence: 99%